Understanding a Dialectical Materialist CHAT Perspective on Social Movement Learning - Peter H. Sawchuk (Adult Education Research Conference, 2014)
This paper addresses adult social movement learning (SML) dynamics. Drawing on a specific dialectical materialist variation of a socio-cultural learning theory called Cultural Historical Activity Theory (CHAT) I explore findings from a large-scale research project in Toronto (Canada) called the Anti-Poverty Community Organizing and Learning (APCOL). I offer some preliminary evidence for the importance of something referred to as “object-work/skill” for discerning differences in anti-poverty activist learning lives.